Medication adherence among Lebanese adult patients with hypothyroidism: Validation of the Lebanese Medication Adherence Scale and correlates - Souheil Hallit; Chadia Haddad; Hala Sacre; Clara Rahme; Marwan Akel; Nadine Saleh; Clarissa Chalhoub; Pascale Salameh (Elsevier, 2021)
Background: A recent scale, the Lebanese Medication Adherence Scale (LMAS-14), was developed and validated among Lebanese patients with hypertension, taking into account variables relating to socio-economic and cultural factors in Lebanon. The LMAS-14 was never validated among patients with chronic diseases other than hypertension. The main goal of this study was to validate the LMAS-14 among Lebanese adult patients with hypothyroidism, compared to the Medication Adherence Rating Scale (MARS). The secondary objectives were to determine factors affecting adherence. Methods: This cross-sectional study was carried out between May and September 2018, and enrolled 244 participants using a proportionate random sample of community pharmacies in all Lebanese governorates. A factor analysis was conducted, in addition to reliability and other validity measures. Results: The optimal LMAS-14 score, considered as a cutoff between controlled and uncontrolled TSH levels, was 10.50 with a sensitivity and a specificity of 93.5% and 90%, respectively. The area under the curve was high: 0.979 [0.958-0.999]; P < 0.001. At this cutoff value, the results showed that 152 (63.3%) patients had good medication adherence. The Cronbach's alpha for the full scale was 0.845. A high ICC was found between the two scales (0.791 ranging from 0.731 to 0.838; p < 0.001). A higher medication adherence was significantly associated with a university level of education (Beta = 1.068) compared to illiteracy. Conclusion: The results of the present study show that the modified LMAS-14 could be considered as a useful tool for measuring medication adherence in patients with hypothyroidism.